Status of Graduate and Professional Education of Women 1974: A Review of the Literature and Bibliography - Oltman, Ruth M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This document reviews the status of graduate and professional education of women for 1974. The first section, a review of the literature, discusses background and current developments, the status of graduate education, reports concerning women in higher education, social factors and attitudes, institutional barriers, trends in specific disciplines, requirements of the law, and proposed solutions. The second section encompasses a 68-item bibliography on graduate and professional education of women. (MJM)
ERIC Note: Paper prepared for the American Association of University Women Conference on Graduate and Professional Education of Women, May 9-10, 1974.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Females; Graduate Study; Higher Education; Laws; Literature Reviews; Professional Education; Sex Discrimination; Social Attitudes; Reference Materials, Bibliographies